IMPLEMENTATION OF THE TALAQQI METHOD TO IMPROVE STUDENTS’ QUR’ANIC READING ABILITY - Khairunnisa; Umi Amelia Putri; Maula Fiqriani; Kasinyo Harto; Ummi Hiras Habisukan (SOSIOEDUKASI, 2026)
This study aims to comprehensively describe the implementation of the talaqqi method in improving students’ Qur’anic reading skills at SMK Negeri 1 Makarti Jaya, Banyuasin Regency, South Sumatra. The background of this research is based on the persistently low level of Qur’anic reading ability among some students in formal schools, particularly in terms of the accuracy of makhraj, the application of tajwid rules, and reading fluency. This study employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The researcher served as the main research instrument, supported by observation guidelines, interview protocols, and an assessment sheet for Qur’anic reading skills. To strengthen the qualitative findings, this study was also complemented by quantitative data in the form of students’ Qur’anic reading assessments before and after the implementation of the talaqqi method, which covered aspects of makhraj and tajwid accuracy, reading fluency, as well as accuracy of pronunciation and recitation rhythm. The results of the study indicate that the implementation of the talaqqi method was carried out through five main stages, namely explaining, demonstrating, imitating, listening, and evaluating. The application of this method emphasizes direct face-to-face interaction between teachers and students, enabling immediate and continuous correction of recitation errors. The findings reveal a significant improvement in students’ Qur’anic reading skills, as reflected in the increase in the average reading score from 58.85 in the pre-implementation stage to 87.29 after the application of the talaqqi method. In addition to enhancing the technical aspects of Qur’anic reading, the talaqqi method also contributes to fostering discipline, patience, responsibility, and students’ respect for teachers and the Qur’an. Therefore, the talaqqi method is proven to be effective and relevant for implementation in Qur’anic learning within formal school settings as an effort to improve recitation quality while simultaneously strengthening students’ religious character.